Organizamos nuestro trabajo para elaborar una revista - Calderon Santos, Melva Seberina (2018)
It expresses its needs, interests, feelings and expressions, adapting its discourse to the different interlocutors, is receptive and shows an attitude of respectful listening with attention and critical spirit to the messages, in the different communicative situations in which it participates. It includes the main ideas of various oral texts, referring to scientific, historical and current affairs. Take notes while listening according to your purpose and using some basic graphic organizers, depending on the communicative situation Shows confidence in expressing interests, needs and expectations that correspond to their age.